1992
DOI: 10.1007/bf02403876
|View full text |Cite
|
Sign up to set email alerts
|

Electron microdiffraction studies of zirconia particles

Abstract: A batch of zirconia was prepared at a pH of 2.95 using a sol-gel technique. The crystal structures formed during 500 ~ calcination was followed by X-ray diffraction. The tetragonal phase was the major component after the initial calcination period of 15.5 h; however, it gradually transformed to the monoclinic crystal form during 200 h of calcination at 500 ~ Electron microdiffraction was employed in the present investigation to determine the crystal structure of individual particles, and to identify whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Following transformation of t-Zr0 2 to m-Zr0 2 many individual particles are observed to be twinned or multiply twinned. 58 The BET surface areas, following 4 hours of calcination at 600 0 e in air, fall within 40 + 10 m 2 /g and show no dependence upon the crystal phase of the calcined material. Thus, similar surface areas are obtained for t-Zr02 and m-Zr0 2 ; this provides an additional measure to show that similar particle sizes are obtained for both materials.…”
Section: °Cmentioning
confidence: 96%
See 3 more Smart Citations
“…Following transformation of t-Zr0 2 to m-Zr0 2 many individual particles are observed to be twinned or multiply twinned. 58 The BET surface areas, following 4 hours of calcination at 600 0 e in air, fall within 40 + 10 m 2 /g and show no dependence upon the crystal phase of the calcined material. Thus, similar surface areas are obtained for t-Zr02 and m-Zr0 2 ; this provides an additional measure to show that similar particle sizes are obtained for both materials.…”
Section: °Cmentioning
confidence: 96%
“…The particle indicated by an arrow in Figure 17 is seen to contain three or four variants in the particle with a diameter of 34 nm. 58 A still unresolved feature of the t -+ m transition in zirconia concerns twinning, which is commonly observed in monoclinic Zr0 2 . Twins are believed to occur in bulk materials to accommodate at least partially the shape change associated with the t -+ m transformation.…”
Section: °Cmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, MEA medium was shown to be advantageous for the confirmation of the putative peptaibol production. Addition of Aib to the growth medium has been shown to induce a higher level of peptaibol production [17]. It is also clear that MEA is a suitable medium for the production of peptaibols by T. asperellum, and this can be enhanced by the presence of a precursor of Aib (Fig.…”
mentioning
confidence: 98%